Ultrastructural study of phenylethanolamine-N-methyltransferase, corticotropin-releasing factor and neurotensin immunoreactive neurons in the external cuneate nucleus of the gerbil - Lan, C.-T. (2016)
10.1016/0006-8993(95)01398-9